Reclaiming Workers’ Voice in Algorithmic Workplaces: Human-Centered HRM Beyond Efficiency Logic - Primantari, Indy Axelina (Generate Digital Publishing, 2025)
Objective: This study aims to synthesize and integrate literature on workers' voice in the context of algorithmic workplaces by placing it in the perspective of human-centered Human Resource Management (HRM), as well as explaining how and under what conditions voice can be maintained or reclaimed beyond the logic of algorithmic efficiency. Research Design & Methods: This study uses a Systematic Literature Review (SLR) approach following the PRISMA protocol. Articles were selected from reputable Q1 journals indexed in Scopus and Web of Science, covering the themes of algorithmic management, workers' voice, and digital HRM. The synthesis process was conducted through thematic and conceptual analysis to identify patterns, mechanisms, and institutional configurations that influence voice in algorithm-mediated work. Findings: The SLR results show that workers' voice in algorithmic workplaces is not inherently reduced by technology, but rather shaped by algorithmic system design and HRM practice configurations. This study identifies variations in voice—ranging from reduced, distorted, to human-centered mediated voice—and highlights the role of HRM in determining the legitimacy, access, and effectiveness of voice. Implications & Recommendations: Theoretically, these findings expand the HRM literature by positioning voice as an institutional construct. Practically, organizations are advised to integrate human-centered HRM principles into algorithmic governance to balance efficiency, fairness, and work well-being. Contribution & Value Added: This article offers an integrative conceptual framework explaining how HRM can play a strategic role in reclaiming workers' voice in the era of algorithm-based work.